Widespread Elevational Occurrence of Antifungal Bacteria in Andean Amphibians Decimated by Disease: A Complex Role for Skin Symbionts in Defense Against Chytridiomycosis - Catenazzi, Alessandro; Flechas, Sandra V.; Burkart, David; Hooven, Nathan D.; Townsend, Joseph; Vredenburg, Vance T. (Frontiers in Microbiology, 2018)
Emerging infectious disease is a growing threat to global health, and recent discoveries reveal that the microbiota dwelling on and within hosts can play an important role in health and disease. To understand the capacity of skin bacteria to protect amphibian hosts from the fungal disease chytridiomycosis caused by Batrachochytrium dendrobatidis (Bd), we isolated 190 bacterial morphotypes from the skin of 28 host species of frogs (families Centrolenidae, Craugastoridae, Hemiphractidae, Hylidae, Leptodactylidae, and Telmatobiidae) collected from the eastern slopes of the Peruvian Andes (540–3865 m a.s.l.) in the Kosñipata Valley near Manu National Park, a site where we previously documented the collapse of montane frog communities following chytridiomycosis epizootics. We obtained isolates through agar culture from skin swabs of wild frogs, and identified bacterial isolates by comparing 16S rRNA sequences against the GenBank database using BLAST. We identified 177 bacterial strains of 38 genera, including 59 bacterial species not previously reported from any amphibian host. The most common bacterial isolates were species of Pseudomonas, Paenibacillus, Chryseobacterium, Comamonas, Sphingobacterium, and Stenotrophomonas. We assayed the anti-fungal abilities of 133 bacterial isolates from 23 frog species. To test whether cutaneous bacteria might inhibit growth of the fungal pathogen, we used a local Bd strain isolated from the mouthparts of stream-dwelling tadpoles (Hypsiboas gladiator, Hylidae). We quantified Bd-inhibition in-vitro with co-culture assays. We found 20 bacterial isolates that inhibited Bd growth, including three isolates not previously known for such inhibitory abilities. Anti-Bd isolates occurred on aquatic and terrestrial breeding frogs across a wide range of elevations (560–3695 m a.s.l.). The inhibitory ability of anti-Bd isolates varied considerably. The proportion of anti-Bd isolates was lowest at mid-elevations (6%), where amphibian declines have been steepest, and among hosts that are highly susceptible to chytridiomycosis (0–14%). Among non-susceptible species, two had the highest proportion of anti-Bd isolates (40 and 45%), but one common and non-susceptible species had a low proportion (13%). In conclusion, we show that anti-Bd bacteria are widely distributed elevationally and phylogenetically across frog species that have persisted in a region where chytridiomycosis emerged, caused a devastating epizootic and continues to infect amphibians.